Estimating the abundance of the Hector's dolphins ( Cephalorhynchus hectori hectori ) that use Porpoise Bay, New Zealand - Max Harvey; Steve Dawson; William Rayment (New Zealand Journal of Marine and Freshwater Research, 2024)
Hector's dolphin, an endangered species endemic to the coastal waters of Aotearoa New Zealand, has a highly fragmented population structure. Low abundance of some local subpopulations, coupled with a stepping‐stone mode of gene flow, suggests that these are at high risk of extinction. During the austral summer, dolphins from the small, genetically distinct subpopulation found along the South Island's south‐east coast frequently use Porpoise Bay, an important foraging and calving area. The estimate of abundance of dolphins using the bay has not been updated since the introduction of protection measures in 2008 intended to mitigate bycatch in fisheries. Photo‐ID surveys, including random photography to estimate mark rate, were conducted during summer 2020. Using Chapman's version of the Lincoln‐Petersen estimator, it was estimated that 63 Hector's dolphins (95% CI = 46–79), including three new calves, used Porpoise Bay during the study period. While regression analyses showed no evidence of change since previous abundance estimates in 1996–97, 2002–03, and 2008, the very low estimated abundance validates fears for the long‐term persistence of this subpopulation. In this context, potential threats need to be managed within a precautionary framework, with a clear goal of facilitating recovery.

Decadal stability in the distribution of bottlenose dolphins in Dusky Sound/Tamatea, New Zealand - Steph Bennington; Marta Guerra; David Johnston; Rohan Currey; Tom Brough; Chloe Corne; Dave Johnson; Shaun Henderson; Elisabeth Slooten; Steve Dawson; Will Rayment (New Zealand Journal of Marine and Freshwater Research, 2023)
Recreational use of wild spaces is increasingly popular, resulting in a burgeoning tourism industry. Such activities can degrade the environment and disrupt the behaviour and natural function of organisms. A small population of bottlenose dolphins ( Tursiops truncatus ) is resident in Dusky Sound, New Zealand, a fjord with increasing human use. Dolphins, as top predators, play an important role within ecosystems and are at risk of long‐term negative consequences from behavioural changes when exposed to high levels of vessel activity. A better understanding of the distribution of the dolphins in Dusky Sound would provide a framework for developing management within the fjord. Here we describe where dolphins were most frequently found, based on >40,000 km of photo‐ID survey effort conducted over 10 years. Kernel density estimation revealed two large core areas that remained consistent over the duration of this study. This information could be used to determine areas within Dusky Sound where human activities around dolphins could be managed to avoid anthropogenically driven detrimental impacts. We suggest the following: (1) establish dolphin protection zones, (2) create a marine mammal sanctuary, (3) extend marine reserve boundaries, and/or (4) lower catch limits for fish within the fjord boundaries.

Size structure of broadnose sevengill sharks ( Notorynchus cepedianus ) in Sawdust Bay, Rakiura/Stewart Island, estimated using underwater stereo‐photogrammetry - Robert Lewis; Steve Dawson; Will Rayment (New Zealand Journal of Marine and Freshwater Research, 2023)
The broadnose sevengill shark ( Notorynchus cepedianus ) is a large marine predator found in temperate coastal marine habitats. Despite being commonly encountered, details of its ecology are limited. To partially address this, we quantified the size and sex structure of N. cepedianus in Paterson Inlet, Stewart Island, New Zealand. A stereo‐camera baited underwater video system (BRUV) was deployed in a shallow coastal embayment to capture underwater video of N. cepedianus for stereo photogrammetric measurement between June 2016 and November 2017. Individual sharks were sexed via observation of claspers. Three‐dimensional underwater calibration of the photogrammetric system, using a precisely measured cube, indicated a mean error of n = 78 individuals, mean = 211.4, S.E. = 2.97). The observed sex ratio was heavily biased, with females making up 95% of the population in winter 2016 and 73% in summer 2017. This study provides new data on N. cepedianus in southern New Zealand as well a non‐invasive, low‐cost methodology that can be applied to other study areas.

Multi‐decadal observations of the size structure of sperm whales at Kaikōura, New Zealand - Toby Dickson; William Rayment; Marta Guerra; Steve Dawson (New Zealand Journal of Marine and Freshwater Research, 2023)
Measurements of body length play an important role in the assessment of size and population structure of whales, allowing estimation of population parameters such as age at sexual and physical maturity. Uniquely, sperm whales can be measured from the interpulse interval (IPI) of their echolocation clicks, which contain information on the length of the head, which is allometrically related to body length. Measurements of IPI were taken from 424 acoustic recordings made between 1996 and 2019 at Kaikōura, New Zealand. Extrapolation to total length, using a new regression equation calculated from this population, revealed a significant increase in the mean length of whales visiting Kaikōura during summer in recent years (2014–2019), with no trend in the mean length for those visiting in winter. Increasing size during summer months appears to be driven by the growth of the same individuals returning summer after summer, combined with declining recruitment of new, smaller individuals. Thus, we hypothesise that the whales that visit in summer may represent an aging population. This is significant as sperm whales are a taonga [Of special significance to NZ Māori] species, top predators in the Kaikōura ecosystem, and the primary focus of the tourism industry at Kaikōura.

Offshore distribution of Hector's dolphins at Banks Peninsula, New Zealand: Is the Banks Peninsula Marine Mammal sanctuary large enough? - Elisabeth Slooten; William Rayment; Steve Dawson (New Zealand Journal of Marine and Freshwater Research, 2006)
Aerial surveys of Hector's dolphins were carried out to evaluate the effectiveness of the Banks Peninsula Marine Mammal Sanctuary. In summer, the proportion of sightings inside the 4 nautical mile offshore boundary of the sanctuary was 79%. This dropped to just over 35% in winter. These estimates were used in a population viability analysis to determine whether the sanctuary needs to be extended to reduce dolphin bycatch to sustainable levels. We followed the standard procedure for setting limits on marine mammal bycatch in the United States to calculate a bycatch limit of 1.6 or 2.8 dolphins per year (depending on whether the sanctuary population is included). If the offshore boundary was extended to 15 nautical miles, the sanctuary would need to be extended alongshore north and south by more than 30 nautical miles to reduce bycatch to 2.8, or north and south by 60 nautical miles to reduce bycatch to 1.6 dolphins per year.

Abundance, residency, and habitat utilisation of Hector's dolphins ( Cephalorhynchus hectori ) in Porpoise Bay, New Zealand - Lars Bejder; Steve Dawson (New Zealand Journal of Marine and Freshwater Research, 2001)
Theodolite tracking and boat‐based photo‐identification surveys were carried out in the austral summers of 1995/96 and 1996/97 to assess abundance, residency, and habitat utilisation of Hector's dolphins (Cephalorhynchus hectori van Beneden 1881) in Porpoise Bay, on the south‐east corner of the South Island of New Zealand. Data are consistent with the model of a small resident population that is visited occasionally by members of neighbouring populations. Mark‐recapture analysis of photographically identified individuals, along with data on the proportion of animals bearing identifying marks, indicates a local population of 48 dolphins (95% CI = 44–55) in 1996/97. Dolphins spent a large proportion of their time in a small area inside the bay. Dolphin sightings were more congregated in successive time periods from early morning to late afternoon. No pattern of diurnal movement into and out of the bay was observed.